Pyrolyzed deketene curcumin controls regulatory T cell generation and gastric cancer metabolism cooperate with 2-deoxy-d-glucose - MaruYama, Takashi; Miyazaki, Hirofumi; Lim, Yun-Ji; Gu, Jian; Ishikawa, Masaki; Yoshida, Taichi; Chen, WanJun; Owada, Yuji; Shibata, Hiroyuki (Frontiers in Immunology, 2023)
Pyrolyzed deketene curcumin GO-Y022 prevents carcinogenesis in a gastric cancer mouse model. However, it is still less clear if GO-Y022 affects tumor-induced immune suppression. In this study, we found that GO-Y022 inhibited Treg generation in the presence of transforming growth factor beta 1 (TGF-β). However, GO-Y022 showed less impact on Foxp3+ Tregs in the gastric tumor microenvironment. Gastric tumor cells produce a large amount of L-lactate in the presence of GO-Y022 and diminish the inhibitory role of GO-Y022 against Treg generation in response to TGF-β. Therefore, naïve CD4+ T cells co-cultured with GO-Y022 treated gastric tumor cells increased Treg generation. GO-Y022-induced tumor cell death was further enhanced by 2-deoxy-d-glucose (2DG), a glycolysis inhibitor. Combination treatment of GO-Y022 and 2DG results in reduced L-lactate production and Treg generation in gastric tumor cells. Overall, GO-Y022-treatment with restricted glucose metabolism inhibits gastric tumor cell survival and promotes anti-tumor immunity.